Pivotal roles of glycogen synthase-3 in hepatocellular carcinoma. (August 2017) - Cervello, Melchiorre; Augello, Giuseppa; Cusimano, Antonella; Emma, Maria Rita; Balasus, Daniele; Azzolina, Antonina; McCubrey, James A.; Montalto, Giuseppe
Abstract: Hepatocellular carcinoma (HCC) is one of the most common cancers in the world, and represents the second most frequently cancer and third most common cause of death from cancer worldwide. At advanced stage, HCC is a highly aggressive tumor with a poor prognosis and with very limited response to common therapies. Therefore, there is still the need for new effective and well-tolerated therapeutic strategies. Molecular-targeted therapies hold promise for HCC treatment. One promising molecular target is the multifunctional serine/threonine kinase glycogen synthase kinase 3 (GSK-3). The roles of GSK-3β in HCC remain controversial, several studies suggested a possible role of GSK-3β as a tumor suppressor gene in HCC, whereas, other studies indicate that GSK-3β is a potential therapeutic target for this neoplasia. In this review, we will focus on the different roles that GSK-3 plays in HCC and its interaction with signaling pathways implicated in the pathogenesis of HCC, such as Insulin-like Growth Factor (IGF), Notch, Wnt/β-catenin, Hedgehog (HH), and TGF-β pathways. In addition, the pivotal roles of GSK3 in epithelial-mesenchymal transition (EMT), invasion and metastasis will be also discussed.